2021
DOI: 10.3390/ijms22179240
|View full text |Cite
|
Sign up to set email alerts
|

Dimer Interface in Natural Variant NK1 Is Dispensable for HGF-Dependent Met Receptor Activation

Abstract: NK1, a splicing variant of hepatocyte growth factor (HGF), binds to and activates Met receptor by forming an NK1 dimer and 2:2 complex with Met. Although the structural mechanism underlying Met activation by HGF remains incompletely resolved, it has been proposed that the NK1 dimer structure participates in this activation. We investigated the NK1 dimer interface’s role in Met activation by HGF. Because N127, V140, and K144 are closely involved in the head-to-tail NK1 dimer formation, mutant NK1 proteins with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…This mutation is a single nucleotide substitution (chr7:81707309G>A, hg19) that introduces a premature STOP codon, causing a truncation of the protein. It is located in the SP domain of the HGF protein, which is the domain responsible for binding to the HGF receptor [18]. This is consistent with previous reports that mostly describe mutations perturbing HGF domains important for interaction with the receptor [11][12][13].…”
Section: Identification Of the Hgf Variant In The Familial Lymphedema...supporting
confidence: 90%
“…This mutation is a single nucleotide substitution (chr7:81707309G>A, hg19) that introduces a premature STOP codon, causing a truncation of the protein. It is located in the SP domain of the HGF protein, which is the domain responsible for binding to the HGF receptor [18]. This is consistent with previous reports that mostly describe mutations perturbing HGF domains important for interaction with the receptor [11][12][13].…”
Section: Identification Of the Hgf Variant In The Familial Lymphedema...supporting
confidence: 90%
“…It then acts as a scaffold, allowing for the transfer of phosphorylated RTKs to the cytoplasm 38 . It has been reported that stimulation with hepatocyte growth factor (HGF), a growth factor that activates Gab1, subsequently activates the ERK1/2 pathway 39 . Gab1 has been reported to be involved in intracellular signaling pathways by fibroblast growth factor (FGF) and epidermal growth factor (EGF) 40 .…”
Section: Discussionmentioning
confidence: 99%